2002
DOI: 10.1046/j.1365-2699.2002.00751.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation at high latitudes: the geography of body size and cranial morphology of the muskox, Ovibos moschatus

Abstract: Aim Bergmann's rule, one of the most studied and controversial ecogeographical generalizations, has rarely been tested with observations from high latitudes. We tested the rule using cranial measurements of the muskox [Ovibos moschatus (Zimmerman)], a homeotherm with an extremely northern distribution. We also used these data to describe geographical patterns in the species' dental architecture, an extension of the framework developed from interspecific comparisons. Location Specimens were compiled from arctic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…According to Bergmann's rule (Bergmann, 1847;Mayr, 1956;James, 1970), within a given species, the body size of a northern race tends to be larger than that of a southern race. Bergmann's rule is a valid ecological generalization for birds and mammals (Lindsey, 1966;Brown & Lee, 1969;Meiri & Dayan, 2003), although exceptions are common (Abe, 1967;Zink & Remsen, 1986;Kaneko, 1988;Smith, Schaefer & Patterson, 2002). Among the mammals of Japan, we expect the body size of northern races, those distributed in Hokkaido, to be larger than those of southern races, those occurring in Honshu, Shikoku and Kyushu.…”
Section: Introductionmentioning
confidence: 94%
“…According to Bergmann's rule (Bergmann, 1847;Mayr, 1956;James, 1970), within a given species, the body size of a northern race tends to be larger than that of a southern race. Bergmann's rule is a valid ecological generalization for birds and mammals (Lindsey, 1966;Brown & Lee, 1969;Meiri & Dayan, 2003), although exceptions are common (Abe, 1967;Zink & Remsen, 1986;Kaneko, 1988;Smith, Schaefer & Patterson, 2002). Among the mammals of Japan, we expect the body size of northern races, those distributed in Hokkaido, to be larger than those of southern races, those occurring in Honshu, Shikoku and Kyushu.…”
Section: Introductionmentioning
confidence: 94%
“…The body size within some vertebrate taxa increase towards the north (Bergman's rule), but there are several notable Arctic exceptions to this (e.g. reindeer (131); muskox (132)) There are few physiological adaptations in homeotherms (i.e. warm blooded) that are unique to Arctic animals.…”
Section: Animal Adaptations To Low Temperaturesmentioning
confidence: 99%
“…Selection may favor much greater thermal tolerances at lower temperatures and greater wind strengths than we could test in captivity at Fairbanks. Interestingly, Smith et al (2002) found no clinal-or temperature-related variation in body size for adult muskoxen across a latitudinal range of 60Њ-83ЊN. This is contrary to Bergmann's rule (see Ashton et al 2000;Smith et al 2002) that endotherms should be larger nearer the poles because selection should favor lower SA : vol ratios that minimize heat loss.…”
Section: Discussionmentioning
confidence: 68%
“…Interestingly, Smith et al (2002) found no clinal-or temperature-related variation in body size for adult muskoxen across a latitudinal range of 60Њ-83ЊN. This is contrary to Bergmann's rule (see Ashton et al 2000;Smith et al 2002) that endotherms should be larger nearer the poles because selection should favor lower SA : vol ratios that minimize heat loss. Lyberth et al (2007) did report spatial differences in body sizes for mature muskoxen, but the effect was most pronounced for males and was attributed to the interplay between resource availability, density dependence, and sexual selection rather than to weather-induced phenotypic variations.…”
Section: Discussionmentioning
confidence: 68%